2014
DOI: 10.1016/j.idcr.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Isolated left upper extremity myositis and severe rhabdomyolysis in an adult with H1N1 Influenza, a case report with literature review

Abstract: Acute viral myositis is a fairly rare condition and usually seen in recovery phase of illness, especially in pediatric or geriatric population. Influenza type A, specifically H1N1 may present with generalized myositis and mild elevation of creatinine kinase in addition to usual manifestations. We would like to discuss an atypical presentation of Type A Influenza (H1N1) in a middle aged male who was never immunized for influenza, presenting with fever, vomiting, anuria and acute severe left upper extremity pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 16 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…Interestingly, many muscle biopsies done for diagnostic purposes are either normal or inconclusive and, in most cases, a virus has not been detected. One study demonstrated the expression of alpha 2,3 and alpha 2,6-linked sialic acid receptors on muscle cells, which are the same as located on respiratory epithelial cells [10,30].…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Interestingly, many muscle biopsies done for diagnostic purposes are either normal or inconclusive and, in most cases, a virus has not been detected. One study demonstrated the expression of alpha 2,3 and alpha 2,6-linked sialic acid receptors on muscle cells, which are the same as located on respiratory epithelial cells [10,30].…”
Section: Discussionmentioning
confidence: 98%
“…Acute viral myositis complicated by rhabdomyolysis is rare but can be a very serious and life-threatening complication of influenza infection which presents itself as a global burden every year [1][2][3][4][5][6][7][8][9][10][11]. It has been defined with the following virus: influenza [1][2][3][4][5][6][7][8][9][10][11][12]15], coxsackievirus [13], Epstein-Barr virus [16], adenovirus [17], echovirus [18], cytomegalovirus [19], measles virus [20], varicella-zoster virus [21], human immunodeficiency virus [22], dengue virus [23], parainfluenza [24], and herpes simplex virus [25]. According to one study, the most common viral agent responsible for viral-induced rhabdomyolysis is the influenza virus reported in 33% of cases [26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations